Single-layer W-coated MoS2 nanosheet as well as preparation method and application thereof

Through the preparation of single-layer W@MoS2 nanosheets, the problems of poor penetration ability and low catalytic activity of photothermal therapy in antibacterial treatment are solved, and efficient photothermal conversion and antibacterial effect are achieved. It is suitable for methicillin-resistant golden yellow The treatment of Staphylococcus avoids damage to cell tissue.

CN119113108AActive Publication Date: 2024-12-13CHINA GENE PHARMVALLEY
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411242091.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-05
Publication Date
2024-12-13
Estimated Expiration
2044-09-05

AI Technical Summary

Technical Problem

Photothermal therapy has problems such as poor penetration ability and low catalytic activity of material ROS in antibacterial therapy, resulting in potential damage to cell tissue and insufficient antibacterial effect, especially in the treatment of methicillin-resistant Staphylococcus aureus.

Method used

Single-layer W@MoS2 nanosheets are prepared by hydrothermal combination method. By adjusting the raw material usage ratio and reaction conditions, the unique morphology and high catalytic activity of the material are ensured, the photothermal absorption capacity and antibacterial effect are enhanced, and the photothermal absorption capacity and antibacterial effect are enhanced. Na2WO4·2H2O is used. Doping modification stimulates the catalytic performance of MoS2 nanosheets, forms peroxidase-like activities, and improves photothermal conversion efficiency.

Benefits of technology

It significantly improves the penetration ability and antibacterial effect of photothermal therapy, reduces damage to cell tissue, and achieves effective bactericidal and wound repair on methicillin-resistant Staphylococcus aureus, avoiding bacterial resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119113108A_ABST
    Figure CN119113108A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of antibacterial two-dimensional nano material Mxene catalysts, and particularly relates to a single-layer W-coated MoS2 nanosheet as well as a preparation method and application thereof. The method comprises the following steps: 1) dissolving water-soluble molybdate and water-soluble tungstate in water, and uniformly mixing to obtain a mixed solution; and 2) adding a sulfur source and an organic solvent into the mixed solution, mixing, reacting, and drying to obtain powder. The single-layer W-coated MoS2 nanosheet has a unique two-dimensional plane structure, is large in specific surface area, shows good optical and electronic properties, and is high in photo-thermal absorption in a near-infrared second region, that is, the photo-thermal conversion efficiency is improved, meanwhile, efficient photo-thermal amplification is achieved through peroxidase-like activity of the single-layer W-coated MoS2 nanosheet material, and the photo-thermal conversion efficiency is improved. And the anti-methicillin-resistant staphylococcus aureus infection treatment can be carried out, and the thermal therapy injury to normal tissues is avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of antibacterial two-dimensional nanomaterial Mxene catalyst, and specifically relates to a single-layer W@MoS2 nanosheet and a preparation method and application thereof. Background Art

[0002] After research, it was found that Staphylococcus aureus is an infectious pathogen. Although it does not cause cell infection, it can cause local and systemic purulent infections after entering the human circulatory system. In particular, methicillin-resistant Staphylococcus aureus (MRSA) was discovered in the 1960s. Methicillin-resistant Staphylococcus aureus contains PBP2a, which is unique to resistant strains, making methicillin-resistant Staphylococcus aureus resistant to penicillin. PBP2a can be induced by β-lactam antibiotics and has a low affinity for β-lactam antibiotics, so it rarely binds to this type of antibiotics. MRSA is ubiquitous and poses a huge challenge to effective medical treatment and infection control, so it is particularly important to eliminate the increasingly serious MRSA. However, traditional antibiotic therapy has been shown to have serious limitations. The World Health Organization has recognized the major threat posed by drug-resistant bacteria to human health because these pathogens can spread rapidly and are difficult to control. Therefore, it is crucial to find a new way to treat drug-resistant bacterial infections.

[0003] Photothermal therapy (PTT) is an innovative antibacterial method that uses near-infrared (NIR) light to induce photothermal agents (PTAs) to kill bacteria by raising their temperature. This method is non-toxic, controllable, highly specific, and has few side effects. However, high-power treatment may damage surrounding cell tissues, while low-power treatment may reduce the antibacterial effect. Therefore, those skilled in the art focus on studying new antimicrobial materials.

[0004] Among antimicrobial materials, inorganic nanoparticles exhibit unique physicochemical properties due to their small size. Among them, nanozymes have been widely used in biosensing, disease treatment, pollutant degradation, and antibacterial therapy due to their inherent stability and low toxicity. Nanozymes can produce reactive oxygen species, including hydroxyl radicals, hydrogen peroxide, and singlet oxygen, through single-electron reduction reactions. Among various enzyme activities, peroxidase activity is the most prominent because it can convert low concentrations of H2O2 into hydroxyl radicals, thereby destroying biofilms and killing bacteria. However, there are very limited reports on inorganic nanomaterials that are both photosensitizers (PTAs) and have nanozyme activity.

[0005] Among them, molybdenum disulfide nanomaterials have peroxidase-like activity and photothermal therapy capabilities, which can achieve rapid and efficient bacterial removal in vitro and wound disinfection in vivo. Although considerable progress has been made in the application of PTT in the near-infrared light I region, the clinical application of these therapies is still limited to a certain extent due to the poor penetration ability and penetration depth of PTT. In summary, a new type of inorganic nanomaterial with nanozyme activity and photosensitivity is the focus of research. Summary of the invention

[0006] Based on the above content, in order to eliminate MRSA with strong drug resistance, the present invention proposes a single-layer W@MoS2 nanosheet and its preparation method and application.

[0007] The objects of the present invention are:

[0008] 1. Overcome the problems of poor tissue penetration of photothermal therapy and low ROS catalytic activity of materials;

[0009] Second, it can effectively enhance the light and heat absorption capacity of the material to avoid damage to cell tissues during PTT antibacterial treatment;

[0010] 3. It can enhance the bactericidal effect of materials.

[0011] To achieve the above objectives, the present invention adopts the following technical solutions.

[0012] A method for preparing a single-layer W@MoS2 nanosheet.

[0013] The method comprises:

[0014] 1) Dissolve water-soluble molybdate and water-soluble tungstate in water and mix them evenly to obtain a mixed solution;

[0015] 2) Adding a sulfur source and an organic solvent to the mixed solution, mixing and reacting, and drying to obtain a powder.

[0016] As a preference,

[0017] Step 1) The water-soluble molybdate is an alkali metal molybdate and / or an alkali metal permolybdate;

[0018] Step 1) The water-soluble tungstate is an alkali metal tungstate and / or an alkali metal pertungstate, and the amount thereof is 0.3-0.4 g / g water-soluble molybdate;

[0019] In step 1), when the water-soluble molybdate and the water-soluble tungstate are dissolved, the amount of water used is 2-5 mL / g water-soluble molybdate.

[0020] As a preference,

[0021] Step 2) the sulfur source is thiourea, and the amount used is 0.30-0.35 g / g water-soluble molybdate;

[0022] Step 2) The organic solvent is oxalic acid, and its usage is 5-5.5 mL / g water-soluble molybdate.

[0023] As a preference,

[0024] Step 2) The reaction is continued at a constant temperature of 180-220° C. for 22-26 hours.

[0025] A single-layer W@MoS2 nanosheet.

[0026] Application of a single-layer W@MoS2 nanosheet,

[0027] The single-layer W@MoS2 nanosheet is used to participate in biochemical catalytic reactions and / or antibacterial and / or promote wound repair.

[0028] As a preference,

[0029] The monolayer W@MoS2 nanosheet is used for in vitro antibacterial and / or wound thermal repair and / or destruction of biofilm and sterilization. In the technical solution of the present invention, a transition metal dihalide is prepared using Na2MoO4·2H2O, thiourea, and C2H2O4·2H2O as raw materials. MoS2 has a unique electronic configuration and structure, and is bound by strong covalent or ionic bonds within the layer, but is loosely bound by weak van der Waals forces between layers. The present invention is prepared by a simple and efficient hydrothermal combination method, which has little environmental pollution and is easy to operate. The specific morphology and unique size of the antibacterial material can ensure that it exerts a good antibacterial effect at a lower concentration. It can not only be deposited on the surface of bacteria to cause membrane permeabilization and directly destroy the cell wall, but also enter the cell and exert a good antibacterial effect by mediating reactive oxygen species. In order to ensure its clear monolayer structure and nanoscale size, the present invention regulates the morphology of the product by changing the raw material dosage ratio and setting different reaction conditions.

[0030] MoS2 has uniform components, continuous growth, and few impurities. The unique layered structure of the material can enhance the mass transfer capacity and ion diffusion capacity. As the amount of molybdenum salt decreases, its interlayer weakness makes the material tend to peel into a few layers or a single layer, but using only a small amount of molybdenum salt will cause the material to present dispersed and irregularly shaped single crystal particles, not continuous nanosheets. More importantly, MoS2 allows certain molecules, atoms or ions to be easily intercalated. When thiourea is converted into ammonium thiocyanate at high temperature and in-situ intercalated into MoS2, the interlayer spacing is widened, further playing a role in optimizing the electronic structure. In-situ intercalation can inhibit the growth of MoS2, reduce the size of the material, expose more active sites, and increase the exposed active edges. Obviously, excessive thiourea will destroy the structure of the material monolayer, excessive ammonium ion intercalation will expand the interlayer spacing of MoS2, and active oxygen clusters will promote the nucleation of the material. At the same time, thiourea inhibits its growth, making the material tend to present a flower-like or flower-ball shape. It was found through testing that not only the crystals cannot grow in the dominant orientation, resulting in serious structural distortion and disconnection of the material, but also unsaturated sulfides are formed.

[0031] To ensure that the obtained nanosheets have high yield, high purity and high crystallization degree, the present invention limits the reaction conditions. According to the research of those skilled in the art, under suitable temperature conditions, MoS2 can retain the 1T phase with more active sites, and the material morphology is regular and the lamellar structure is clear. Too low a reaction temperature can cause the product to agglomerate, the product particle size is too large, the interlayer bonding force of the layered nanosheets is weak, and the damaged structure can affect the application of the material in the antibacterial process. Too high a temperature can cause M0O2 and MoO3 to appear in the product, the effective conversion rate is significantly reduced, and the antibacterial activity is weakened.

[0032] MoS2 nanosheets have high catalytic activity, and their active sites are located at the edge of the material, but the basal activity is poor, and using them alone will cause the active oxygen clusters to be unstable and consumed too quickly, affecting the antibacterial effect of the material. In order to make full use of the advantages of single-layer two-dimensional materials, the present invention modifies the MoS2 nanosheets by doping with Na2WO4·2H2O atoms to stimulate the active sites on the basal surface and increase their catalytic performance. Alkali metal tungsten atoms are small in size and highly reactive, and can be effectively doped into the interlayer to form intercalation compounds. The substitution of alkali metal tungsten atoms causes structural changes in the material, produces new phases, provides more active centers, improves the catalytic activity of MoS2, enhances the electron transfer ability, and promotes the generation of 1T-type MoS2. Tungsten atoms accelerate the reversible transformation of polysulfides, avoid sulfur passivation, and improve the catalytic activity of W@MoS2. At the same time, tungsten atom doping provides the material with more microporous structures, increases the specific surface area of ​​the material, and achieves a better confinement effect.

[0033] Exogenous active sites and graphene-like layered structures make the monolayer W@MoS2 nanosheets have peroxidase-like activity, which can locally catalyze low-concentration hydrogen peroxide and produce hydroxyl radicals, and can show high photothermal conversion efficiency and photothermal stability under near-infrared light irradiation. Its peroxidase-like active sites accelerate the oxidation reaction in bacteria, consume antioxidant biomolecules, and lead to the accumulation of reactive oxygen species with high antibacterial properties.

[0034] The single-layer W@MoS2 nanosheet has antibacterial drug carrier properties and photodynamic antibacterial activity, and is suitable for the preparation of drug-resistant bacteria inhibitors, drug-resistant bacteria biofilm inhibitors, and subcutaneous drug-resistant bacteria infection abscess therapeutic agents. The material activates oxygen atoms through the sensitization of light of a specific wavelength, and a charge transition from O to Mo occurs. The activated high-energy oxygen can play a bactericidal role. It was found through testing that the photothermal performance and efficiency of W@MoS2 prepared by the present invention are significantly improved. The significant improvement in photothermal performance improves the effectiveness of chemical dynamics, overcomes the problem of insufficient effect of chemodynamic therapy, and produces a stronger synergistic antibacterial effect. Photothermal therapy using W@MoS2 can effectively prevent bacteria from developing drug resistance and reduce damage to cell tissues, providing a feasible strategy for the effective treatment of wounds infected with methicillin-resistant Staphylococcus aureus, and also provides a reliable direction for the design and application of two-dimensional nanomaterial Mxene catalysts.

[0035] The beneficial effects of the present invention are as follows:

[0036] (1) The single-layer W@MoS2 nanosheet material based on the two-dimensional nanomaterial Mxene has peroxidase-like catalytic activity, which can effectively overcome the problems of poor tissue penetration of photothermal therapy and low ROS catalytic activity of the material;

[0037] (2) The monolayer W@MoS2 nanosheet has a unique two-dimensional planar structure with a large specific surface area, exhibiting good optical and electronic properties, and high photothermal absorption in the near-infrared region II, that is, the photothermal conversion efficiency is improved. At the same time, the peroxidase-like activity of the monolayer W@MoS2 nanosheet material realizes efficient photothermal amplification, which can be used to treat methicillin-resistant Staphylococcus aureus infection and avoid thermal damage to normal tissues.

[0038] (3) Single-layer W@MoS2 nanosheets can achieve both mild antibacterial properties and good antibacterial effects. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 This is a synthesis model diagram of single-layer W@MoS2 nanosheets.

[0040] Figure 2 This is a characterization diagram of the single-layer W@MoS2 nanosheet in Example 1.

[0041] Figure 3 This is a photothermal and nanozyme performance test diagram of the single-layer W@MoS2 nanosheet in Example 1.

[0042] Figure 4 This is a test diagram of the antibacterial performance of the single-layer W@MoS2 nanosheet in Example 1.

[0043] Figure 5 This is a tissue wound surface characterization diagram of a single-layer W@MoS2 nanosheet in Example 1.

[0044] The present invention is further described in detail below in conjunction with specific embodiments and the accompanying drawings. A person of ordinary skill in the art will be able to implement the present invention based on these descriptions. In addition, the embodiments of the present invention involved in the following description are generally only embodiments of a part of the present invention, rather than all embodiments. Therefore, based on the embodiments of the present invention, all other embodiments obtained by a person of ordinary skill in the art without making creative work should fall within the scope of protection of the present invention.

[0045] Unless otherwise specified, the raw materials used in the examples of the present invention are all commercially available or available to those skilled in the art; unless otherwise specified, the methods used in the examples of the present invention are all methods known to those skilled in the art.

[0046] Example 1

[0047] A method for preparing a single-layer W@MoS2 nanosheet, the method comprising:

[0048] 1) Dissolve 10 g Na2MoO4·2H2O and 3 g Na2WO4·2H2O in 30 mL water and mix well to obtain a mixed solution;

[0049] 2) Add 3 g of thiourea and 15 mL of C2H2O4·2H2O to the mixed solution, mix, and keep at a constant temperature of 180°C for 26 h, and dry to obtain a powder.

[0050] The characterization of the single-layer W@MoS2 nanosheet of the present invention is as follows.

[0051] 1.TEM analysis and EDS analysis:

[0052] The double-beam electron microscope DB500 was used to analyze the morphology of the material in this example.

[0053] 2.UV-vis-NIR analysis:

[0054] The photothermal performance of the material in this example was tested using a Cary 5000 UV-Vis-NIR spectrophotometer.

[0055] 3. Biocatalytic performance analysis:

[0056] 3,3',5,5'-Tetramethylbenzidine (TMB) and o-phenylenediamine (OPD) were used as probes to monitor hydroxyl radicals and analyze the catalytic performance in the presence of hydrogen peroxide, respectively.

[0057] The characterization results are as follows.

[0058] like Figure 2 As shown in the figure, W@MoS2 has a single-layer structure, which is composed of a large number of nanometals and has a certain degree of shrinkage, that is, it has the common characteristics of single-layer nanosheets. W@MoS2 has polycrystalline characteristics, and the corresponding plane has obvious diffraction rings. Mo, S and W elements coexist. C, Mo, W, S and O are present in the sample. The characteristic binding energies of Mo 3d3 / 2 and Mo 3d5 / 2 are 232.5eV and 229.4eV, respectively, confirming that Mo 4+ The existence of W·4f 7 / 2 and W·4f 5 / 2 The binding energies of W·5P5 / 2 and W·5P5 / 2 are 31.75eV and 33.95eV respectively. 4+ In addition, the S 2p of divalent sulfur ion was also found at 162.25 eV. 1 / 2 and S2p 3 / 2 From these characterization results, it can be seen that the present invention successfully prepared single-layer W@MoS2 nanosheets.

[0059] like Figure 3 As shown in the figure, W@MoS2 has a wide absorption range for NIR-II laser energy, which is proportional to the increase in W@MoS2 concentration. W@MoS2 with different concentrations (0, 50, 100 μg / mL) was used to absorb NIR-II laser (1064 nm, 1.0 W·cm -2 After irradiation for 6 min, it was found that the temperature of W@MoS2 increased significantly with the increase of concentration, irradiation time and laser power density. -2 Under the condition of 100 μg / mL W@MoS2, the temperature rises to 49 °C. This shows that W@MoS2 exhibits good photothermal performance under NIR-II light irradiation.

[0060] To further evaluate the photothermal efficiency, the W@MoS2 suspension was heated in the near-infrared region II (1064 nm, 1.0 W cm -2 , 6min) were performed for 5 heating / cooling cycles, and the photothermal performance was stable throughout the cycle. The heating / cooling curves showed a photothermal conversion efficiency (η) of 36.9%. These results show that W@MoS2 has a high photothermal conversion efficiency under NIR-II.

[0061] The absorbance of TMB at 652 nm increases with the increase of W@MoS2 concentration and the exposure in the second near-infrared region (1064 nm, 1.0 W·cm -2 , 0~10min). This indicates the inherent biocatalytic activity of W@MoS2, and the catalytic efficiency is significantly improved due to the improved reaction kinetics.

[0062] The catalytic activity of the catalyst was further evaluated using OPD. Similar phenomena as TMB were observed using the OPD probe, confirming and demonstrating the intrinsic biocatalytic activity of W@MoS2. To further verify that NIR-II can enhance biocatalysis, the activity of W@MoS2 and the absorption of OPD at 420nm were compared in the presence and absence of NIR-II. This showed that the production of ROS was significantly increased in the presence of NIR-II. Compared with MoS2, W@MoS2 has better biocatalytic activity and photothermal effect.

[0063] The material in this example is tested for performance, and the testing method is as follows.

[0064] I) In vitro bactericidal performance:

[0065] Ia) Take 100 μL of methicillin-resistant Staphylococcus aureus and prepare a solution with a concentration of 10 6 CFU / mL of bacterial solution was dropped into the well plate, 0.1mmol / L hydrogen peroxide was prepared, 0.1mL hydrogen peroxide was added for every milliliter of bacterial solution, the concentration of the bacterial solution was tested, and the sterilization rate of the material was calculated.

[0066] Ib) Take 100 μL of methicillin-resistant Staphylococcus aureus and prepare a solution with a concentration of 10 6 CFU / mL bacterial solution was dropped into the well plate, W@MoS2 and water were taken to prepare a 100 μg / mL W@MoS2 aqueous solution, and 0.1 mL of W@MoS2 aqueous solution was added per mL of bacterial solution. The wavelength was 1064 nm and the intensity was 1 W·cm -2 The samples were irradiated with laser for 6 minutes and cultured at 37-38℃ for 12 hours. The concentration of bacterial solution was detected and the sterilization rate of the materials was calculated.

[0067] Ic) Mix the above 0.1mmol / L hydrogen peroxide and 100μg / mL W@MoS2 aqueous solution, repeat the test, detect the bacterial solution concentration, and calculate the sterilization rate of the material.

[0068] Id) Mix the above 0.1 mmol / L hydrogen peroxide and 100 μg / mL W@MoS2 aqueous solution and repeat the test at a wavelength of 1064 nm and an intensity of 1 W·cm -2 The samples were irradiated with laser for 6 minutes and cultured at 37-38℃ for 12 hours. The concentration of bacterial solution was detected and the sterilization rate of the materials was calculated.

[0069] The results are as follows.

[0070] Sterilization rate (Ia) Bactericidal rate (Ib) Sterilization rate (Ic) Sterilization rate (Id) 31.4% 34.7% 39.6% 44.1%

[0071] Before the test, the inhibitory effect of different concentrations of hydrogen peroxide (0.0025, 0.05, 0.1, 0.2, 0.4 and 0.8 μg / mL) on methicillin-resistant Staphylococcus aureus was studied, and the results showed that 0.1 mmol / L of hydrogen peroxide was sufficient to produce good antibacterial activity. The same is true for W@MoS2 aqueous solution, and the results show that 100 μg / mL of W@MoS2 aqueous solution is sufficient to produce good antibacterial activity. In addition, hydrogen peroxide easily affects the efficiency of wound healing, so it is necessary to convert hydrogen peroxide into ·OH.

[0072] According to the results in the above table, it can be analyzed that W@MoS2 has significant photothermal activity, and W@MoS2 does have the properties of nanozymes, which can decompose H2O2 into ·OH, thus proving its bactericidal ability. At the same time, the number of colonies in group Id) was significantly reduced, indicating that the photothermal effect can promote the activity of nanozymes, thereby producing higher bactericidal activity.

[0073] II) Wound thermal damage repair test:

[0074] The mouse back cell abscess model was established and divided into 5 groups (I: PBS buffer, II: 100 μg / mL MoS2+0.1 mmol / L H2O2 aqueous solution with an auxiliary strength of 1 W·cm -2 NIR-II: MoS2+H2O2+NIR-II, III: 100μg / mL W@MoS2+0.1mmol / L H2O2 aqueous solution, denoted as W@MoS2+H2O2, IV: 100μg / mL W@MoS2 aqueous solution with an auxiliary coordination strength of 1W·cm -2 NIR-II, denoted as W@MoS2+NIR-II, V: 100 μg / mL W@MoS2+0.1 mmol / L H2O2 aqueous solution auxiliary coordination strength is 1 W·cm -2 The local temperature changes of PBS and W@MoS2 under 1064nm near-infrared irradiation were recorded by a thermal imager.

[0075] The results are as follows.

[0076] In the wound thermal damage repair test, the weight changes of rats were recorded for 7 days, and no obvious abnormalities were found. After 6 minutes of irradiation, the wound temperature rose rapidly from 28°C to 49.8°C, while the temperature change in the PBS group was not obvious, indicating that W@MoS2 has excellent photothermal properties. Figure 5 As shown in the figure, representative wound photos on days 0, 1, 3, 5, and 7 showed that all mice developed wound infection during the treatment period. However, compared with the PBS group, the MoS2+H2O2 group did not accelerate wound healing, and the wound symptoms were still obvious on the 7th day. There was still obvious abscess in the wound of the PBS group, and the wound healing was slow. The wound healing speed of the W@MoS2+H2O2+NIR-II treatment group was the fastest and the edema was the smallest. The above results show that the temperature increase caused by 1064nm laser irradiation is unlikely to burn normal cell tissues, and 50℃ is close to the optimal temperature of the enzymatic reaction.

[0077] Wound healing occurred on the 5th day in the W@MoS2+H2O2 and W@MoS2+NIR-II groups and was enhanced to varying degrees on the 7th day. The relative wound area of ​​the W@MoS2+H2O2+NIR-II group was significantly smaller than that of the PBS group, indicating that the W@MoS2+H2O2+NIR-II group promoted the healing of abscess wounds. After 7 days of treatment, the colony map and quantitative colony count analysis of the W@MoS2+H2O2+NIR-II group showed that the number of bacteria was the lowest compared with other groups, indicating that

[0078] The W@MoS2+H2O2+NIR-II group accelerated wound healing through effective antibacterial activity. In summary, under the synergistic effect of PTT and peroxidase, the W@MoS2+H2O2+NIR-II method can be effectively used for the treatment of wound injuries infected by drug-resistant bacteria.

[0079] III) Anti-biofilm test:

[0080] Based on test I), 6 groups of comparative experiments were performed: I: PBS buffer, II: 0.1mmol / L H2O2 aqueous solution, denoted as H2O2, III: 100μg / mL MoS2 aqueous solution, denoted as MoS2, IV: 100μg / mL MoS2+0.1mmol / L H2O2 aqueous solution, denoted as MoS2+H2O2, V: 100μg / mL W@MoS2 aqueous solution, denoted as W@MoS2, VI: 100μg / mL W@MoS2+0.1mmol / LH2O2 aqueous solution, denoted as W@MoS2+H2O2. The residual biofilm was stained with crystal violet, and the absorbance was measured at 590nm to quantify the biofilm survival rate.

[0081] The results are as follows.

[0082] Since both PTT and nanozymes can destroy biofilms and kill bacteria, the present invention further evaluates the antibacterial ability of W@MoS2 through the W@MoS2 anti-biofilm test. The results show that the W@MoS2+H2O2+NIR-II group has the strongest destructive effect on biofilms, and the biofilm survival rate drops below 30%. By quantifying the fluorescence intensity through CLSM, the W@MoS2+H2O2+NIR-II group exhibits strong red fluorescence, indicating that W@MoS2+H2O2+NIR-II can effectively remove methicillin-resistant Staphylococcus aureus. In addition, the PBS-treated methicillin-resistant Staphylococcus aureus showed a round morphology and a smooth surface, and the surface of the MoS2+H2O2 group had slight wrinkles but no damage. The methicillin-resistant Staphylococcus aureus in the group containing W@MoS2 all showed varying degrees of damage, namely cell wall damage and cytoplasm outflow. Among them, the W@MoS2+NIR-II+H2O2 group showed the most severe cell wall damage and cytoplasm outflow. In summary, W@MoS2 has strong antibacterial potential due to the nanozyme and photothermal properties, and the W@MoS2+H2O2+NIR-II group has good antibiofilm activity against methicillin-resistant Staphylococcus aureus.

[0083] Example 2

[0084] A method for preparing a single-layer W@MoS2 nanosheet, the method comprising:

[0085] 1) Dissolve 10 g Na2MoO4·2H2O and 3 g Na2WO4·2H2O in 30 mL water and mix well to obtain a mixed solution;

[0086] 2) Add 3 g of thiourea and 15 mL of C2H2O4·2H2O to the mixed solution, keep the mixture at a constant temperature of 200°C for 24 h, and dry to obtain a powder.

[0087] The material in this example was tested in the same manner as in Example 1, and the results are as follows.

[0088]

[0089] The present invention prepares a single-layer W@MoS2 nanosheet through a simple and efficient hydrothermal combination method. The nanosheet has high yield, purity and crystallization. Characterization shows that the single-layer W@MoS2 nanosheet retains the 1T phase with more active sites, and has a regular morphology and a clear layer structure. It is deposited on the surface of bacteria to cause membrane permeabilization, has a stronger ability to penetrate tissue cells, and has an improved bactericidal effect. According to the experimental results, within the optimal temperature range of the enzymatic reaction, W@MoS2 can significantly improve the removal of bacteria from the wound, and the wounds of mice begin to heal within 4 to 5 days, indicating that W@MoS2 shows high activity in stimulating tissue cell proliferation and promoting wound healing.

[0090] In the anti-biofilm test, the group containing W@MoS2 had a stronger destructive effect on the biofilm, the biofilm survival rate dropped to below 30%, and the methicillin-resistant Staphylococcus aureus showed obvious cell wall damage and cytoplasm outflow. Compared with Example 1, the cell structure was severely damaged and the cell wall completely lost its supporting effect, indicating that W@MoS2 has significant anti-biofilm activity against methicillin-resistant Staphylococcus aureus.

[0091] Based on the above experimental results, it can be analyzed that the photothermal performance and efficiency of single-layer W@MoS2 nanosheets are significantly improved, thereby improving the effectiveness of chemical kinetics and producing a stronger synergistic antibacterial effect. Photothermal therapy using W@MoS2 can effectively prevent bacteria from developing drug resistance and reduce damage to cell tissues, providing a feasible strategy for the effective treatment of wounds infected with methicillin-resistant Staphylococcus aureus.

[0092] Example 3

[0093] A method for preparing a single-layer W@MoS2 nanosheet, the method comprising:

[0094] 1) Dissolve 10 g Na2M0O4·2H2O and 3 g Na2WO4·2H2O in 30 mL water and mix well to obtain a mixed solution;

[0095] 2) Add 3 g of thiourea and 15 mL of C2H2O4·2H2O to the mixed solution, keep the mixture at a constant temperature of 220°C for 22 h, and dry to obtain a powder.

[0096] The material in this example was tested in the same manner as in Example 1, and the results are as follows.

[0097]

[0098] According to the results in the above table, it can be seen that the bactericidal effect of W@MoS2 nanosheets on methicillin-resistant Staphylococcus aureus has decreased. In the anti-biofilm test, the biofilm survival rate is about 30%, and the degree of bacterial damage is not as good as in Example 2. The reason is that the higher temperature causes MoO2 and MoO3 to appear in the product, which reduces the effective conversion rate of the MoS2 structure, thereby weakening the antibacterial activity.

[0099] Example 4

[0100] A method for preparing a single-layer W@MoS2 nanosheet, the method comprising:

[0101] 1) Dissolve 10 g Na2MoO4·2H2O and 4 g Na2WO4·2H2O in 30 mL water and mix well to obtain a mixed solution;

[0102] 2) Add 3 g of thiourea and 15 mL of C2H2O4·2H2O to the mixed solution, keep the mixture at a constant temperature of 200°C for 24 h, and dry to obtain a powder.

[0103] The material in this example was tested in the same manner as in Example 1, and the results are as follows.

[0104]

[0105] According to the results in the above table, the amount of tungsten salt used in this example is increased, and relatively speaking, the amount of molybdenum salt used is reduced. According to the research of those skilled in the art, the interlayer weakness of MoS2 makes the material tend to peel into a few layers or a single layer, which further causes the material to present dispersed and irregularly shaped single crystal particles. In other words, the components in the W@MoS2 nanosheets in this example are uneven, and compared with Example 2, its mass transfer capacity and ion diffusion capacity are poor, and various properties are significantly reduced.

[0106] Comparative Example 1

[0107] A method for preparing a single-layer W@MoS2 nanosheet, the method comprising:

[0108] 1) Dissolve 10 g Na2MoO4·2H2O and 3 g Na2WO4·2H2O in 30 mL water and mix well to obtain a mixed solution;

[0109] 2) Add 3 g of thiourea and 15 mL of C2H2O4·2H2O to the mixed solution, keep the mixture at a constant temperature of 160°C for 30 h, and dry to obtain a powder.

[0110] The material in this example was tested in the same manner as in Example 1, and the results are as follows.

[0111]

[0112] According to the results in the above table, it can be seen that the bactericidal performance of W@MoS2 nanosheets has decreased, and the cytoplasmic outflow is less. The reason is that the lower reaction temperature will cause the product to agglomerate, the product particle size is too large, the interlayer bonding force of the layered nanosheets is weak, and the structure of this material is prone to failure, thus affecting the application of the material in the antibacterial process. W@MoS2 with a large particle size is more stable, indicating that it has fewer exposed active sites.

[0113] Comparative Example 2

[0114] A method for preparing a single-layer MoS2 nanosheet, the method comprising:

[0115] 1) Dissolve 10 g of Na2M0O4·2H2O in 30 mL of water and mix well to obtain a mixed solution;

[0116] 2) Add 3 g of thiourea and 15 mL of C2H2O4·2H2O to the mixed solution, keep the mixture at a constant temperature of 200°C for 24 h, and dry to obtain a powder.

[0117] The material in this example was tested in the same manner as in Example 1, and the results are as follows.

[0118]

[0119] According to the results in the table, there are few active sites on the basal surface of MoS2 nanosheets. In this case, no atomic doping modification was performed, resulting in fewer active centers in the material and poor catalytic performance. The MoS2 material presents a stable 2H type, which slows down the electron transfer rate, and sulfur is easily passivated, which improves the catalytic stability of the material. The photothermal activity of MoS2 is insufficient. In the wound thermal damage repair test, it can be clearly analyzed that the wound healing speed of the MoS2+H2O2 group and the MoS2+H2O2+NIR-II group is slow, and the abscess is more obvious. Lasers can easily burn normal cell tissues. In addition, the anti-biofilm activity of the material in this case is poor, and the degree of damage to cells is obviously not as good as that of W@MoS2 nanosheets.

[0120] Comparative Example 3

[0121] A method for preparing W@graphene, the method comprising:

[0122] 1) Disperse 10 g of graphene and 3 g of WCl6 in 30 mL of ethanol and mix well to obtain a mixed solution;

[0123] 2) Add 3 g of thiourea and 15 mL of C2H2O4·2H2O to the mixed solution, keep the mixture at a constant temperature of 200°C for 24 h, and dry to obtain a powder.

[0124] The material in this example was tested in the same manner as in Example 1, and the results are as follows.

[0125]

[0126] The material obtained in this example is W@graphene. Although the structure of this material is similar to that of W@MoS2 nanosheets, and it also has abundant exogenous active sites and a peroxidase-like structure, there are abundant negatively charged oxygen-containing functional groups on the surface of graphene, while W 6+ The oxygen-containing functional groups are adsorbed on the graphene surface through electrostatic interactions, and after alcoholysis, WO3 is generated in situ by dehydration at high temperature. However, there are hydrogen bonds between -OH, H2O and WO3, which leads to incomplete dehydration of the product and the formation of trace WO3·xH2O impurities. There are COW bonds between WO3 and graphene, resulting in many defects. The edges of the nanosheets are severely curled, and a considerable number of flower ball-shaped aggregates are produced. The components are not uniform, and the material shows poor antibacterial effect and anti-biofilm activity.

[0127] Comparative Example 4

[0128] A method for preparing a single-layer W@MoS2 nanosheet, the method comprising:

[0129] 1) Dissolve 10 g Na2MoO4·2H2O and 3 g Na2WO4·2H2O in 30 mL water and mix well to obtain a mixed solution;

[0130] 2) Add 4 g of thiourea and 15 mL of C2H2O4·2H2O to the mixed solution, keep the mixture at a constant temperature of 200°C for 24 h, and dry to obtain a powder.

[0131] The material in this example was tested in the same manner as in Example 1, and the results are as follows.

[0132]

[0133] In this case, excessive thiourea will destroy the structure of the material monolayer, excessive ammonium ion intercalation will expand the interlayer spacing of MoS2, and the active oxygen clusters will promote the nucleation of the material. At the same time, thiourea will inhibit its growth, making the material tend to present a flower-like or flower-ball shape. It was found through testing that not only the crystals cannot grow in a dominant orientation, resulting in serious structural distortion and disconnection of the material, but also unsaturated sulfides are formed. MoS2 nanosheets have high catalytic activity, and their active sites are located at the edge of the material, but the basal activity is poor, and using them alone will cause the active oxygen clusters to be unstable and consumed too quickly, affecting the antibacterial effect of the material.

[0134] Comparative Example 5

[0135] Commercially available Ag@MoS2 material.

[0136] The performance test of the material in Example 2 and this example was carried out, and the test method was as follows.

[0137] Long-term antibacterial experiment:

[0138] Take 100 μL of methicillin-resistant Staphylococcus aureus and prepare a 10 6 CFU / mL of bacterial solution was dripped into the well plate, and the material was taken and a solution with a concentration of 100 μg / mL was prepared with PBS buffer solution (pH=7), which was divided into two groups, A and B. Group A was the W@MoS2 material of Example 2, and group B was the Ag@MoS2 material selected in this example. The solution was left to stand for 5 days, and the supernatant of the solution was taken every day. 0.1 mL of the solution was added to the well plate per mL of bacterial solution, and the survival rate of methicillin-resistant Staphylococcus aureus was detected and calculated.

[0139] The results are as follows.

[0140] Group A Day 1 Day 2 Day 3 Day 4 Day 5 Survival rate 0.4% 1.0% 4.6% 5.7% 8.9% Group B Day 1 Day 2 Day 3 Day 4 Day 5 Survival rate 0.7% 1.5% 7.9% 14.5% 22.4%

[0141] According to the results in the above table, the commercially available Ag@MoS2 material can release bactericidal ions, has a good antibacterial effect in a short period of time, and has a large specific surface area and good biocompatibility, which can promote oxidative stress and destroy bacterial cell walls. In particular, the formation of Ag-S bonds can slow down the bactericidal ion Ag in a certain period of time. + ions are released. However, Ag + The combination of ions and MoS2 is poor, the toxicity caused by instantaneous burst release is difficult to solve, and it will also agglomerate, thus affecting the bactericidal effect. In addition, the cost of this material is obviously too high, and its prospects in the field of antibacterial materials are not as good as the material of the present invention.

Claims

1. A method for preparing a single-layer W@MoS2 nanosheet, characterized in that: The method comprises: 1) Dissolve water-soluble molybdate and water-soluble tungstate in water and mix them evenly to obtain a mixed solution; 2) Adding a sulfur source and an organic solvent to the mixed solution, mixing and reacting, and drying to obtain a powder.

2. The method for preparing a single-layer W@MoS2 nanosheet according to claim 1, characterized in that: Step 1) The water-soluble molybdate is an alkali metal molybdate and / or an alkali metal permolybdate; Step 1) The water-soluble tungstate is an alkali metal tungstate and / or an alkali metal pertungstate, and the amount thereof is 0.3-0.4 g / g water-soluble molybdate; In step 1), when the water-soluble molybdate and the water-soluble tungstate are dissolved, the amount of water used is 2-5 mL / g water-soluble molybdate.

3. The method for preparing a single-layer W@MoS2 nanosheet according to claim 1, characterized in that: Step 2) the sulfur source is thiourea, and the amount used is 0.30-0.35 g / g water-soluble molybdate; Step 2) The organic solvent is oxalic acid, and its usage is 5-5.5 mL / g water-soluble molybdate.

4. The method for preparing a single-layer W@MoS2 nanosheet according to claim 1 or 3, characterized in that: Step 2) The reaction is continued at a constant temperature of 180-220° C. for 22-26 hours.

5. A single-layer W@MoS2 nanosheet prepared by the method of any one of claims 1 to 4.

6. An application of the single-layer W@MoS2 nanosheet as claimed in claim 5, characterized in that: The single-layer W@MoS2 nanosheet is used to participate in biochemical catalytic reactions and / or antibacterial and / or promote wound repair.

7. The use of a single-layer W@MoS2 nanosheet according to claim 6, characterized in that: The single-layer W@MoS2 nanosheet is used for in vitro antibacterial and / or wound thermal repair and / or biofilm destruction and sterilization.

Citation Information

Patent Citations

  • Nano-molybdenum sulfide antibacterial material and synthetic method thereof and application thereof

    CN105948124A

  • Preparation method of single-layer or fewer-layer WS2 (tungsten disulfide) nanosheet

    CN106745272A

  • Tungsten-doped molybdenum disulfide material and synthetic method thereof

    CN106994357A

  • Preparation method of MoS2 / WS2 nanolayer composite material

    CN107235511A

  • Preparation method of molybdenum disulfide / MXene layered composite wave-absorbing material

    CN107660114A